2013
DOI: 10.1002/rnj.62
|View full text |Cite
|
Sign up to set email alerts
|

Preferences for rehabilitation services among women with major limb amputations

Abstract: Purpose: We present five cases of adult females with major limb amputations, their concerns and preferences for services across the life span. Design: A convenience sample of five veteran and nonveteran women aged 19-58 with major limb amputations participating in a regional VA Prosthetics Conference in 2010 took part in a panel interview. Findings: The concerns identified by these women as high priorities included independence and participation in a full range of life activities, limitations in access, patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 4 publications
2
17
2
Order By: Relevance
“…These findings are consistent with earlier reports that women with upper limb amputation were more likely to reject devices outright and never use them 10,29 . Women in prior studies have expressed preferences for, and challenges in obtaining, appropriately gendered prostheses that are smaller sized and look more feminine 30–32 …”
Section: Discussionsupporting
confidence: 89%
“…These findings are consistent with earlier reports that women with upper limb amputation were more likely to reject devices outright and never use them 10,29 . Women in prior studies have expressed preferences for, and challenges in obtaining, appropriately gendered prostheses that are smaller sized and look more feminine 30–32 …”
Section: Discussionsupporting
confidence: 89%
“…Historically, prosthetic componentry has been largely designed to accommodate male build and body mass 12 . While we did not find significant differences in self‐reported socket comfort between males and females at the time of the evaluation ( Z = −0.466, P = 0.642), other prosthesis‐related issues (eg, heavy weight, poor suspension, malalignment) may be more prevalent among females 28 and may increase demands on the intact limb or low back. Further investigation into relationships among pain, sex, and prosthetic fit and functionality may help identify mechanisms underlying sex‐specific differences in secondary pain prevalence.…”
Section: Discussioncontrasting
confidence: 59%
“…transfemoral compared with transtibial levels). [7][8][9] Through qualitative analyses, Murray 5 reported that cosmesis may be prioritized partially in relation to etiology and gender, with the latter being counter to Miller's 7 findings, but in agreement with Elnitsky et al 10 It seems plausible that certain demographic variables are related to body image perception. However, based on previous studies which used standardized survey instruments and qualitative analyses, demographic differences are not eminently clear.…”
mentioning
confidence: 80%